Rapid Consumption Method and Poverty and Inequality Estimation in Somalia Revisited - Takamatsu, Shinya; Yoshida, Nobuo; Kotikula, Aphichoke (Washington, DC: World Bank, 2022)
This paper presents updated poverty and inequality estimates from the Somalia High Frequency Survey. This survey used the Rapid Consumption Method to collect consumption data quickly in an environment of high insecurity. Its poverty estimation, therefore, requires imputation of skipped consumption modules. Previous poverty estimates did not properly impute consumption, resulting in the imputation of negative total consumption values for some households.  This paper uses the Two-Part Multiple Imputation method to address this issue. The assessment of module-level prediction performance demonstrates that the Two-Part Multiple Imputation handles this issue effectively. In addition, this paper adopts the newly updated 2011 purchasing power parities to convert the High Frequency Survey consumption data for global poverty measurement purposes. Lastly, this paper provides new inequality measures to address issues with the previous exercise. The paper finds that new poverty rates are slightly lower than those using the previous method while inequality is higher with the new method.